Exploring core food accessibility in Tamworth, NSW, Australia. (1st October 2020) - Payne, Ellen; Brown, Leanne J; Crowley, Elesa; Rollo, Megan; Schumacher, Tracy L
ABSTRACT: Introduction: A lack of core food accessibility negatively affects diet quality, potentially increasing the prevalence of health risk factors such as obesity. The purpose of this study was to investigate core food access in an Australian regional center through the use of data visualization techniques. Methods: Supermarkets were used as a proxy for core food accessibility and were identified and mapped by town region with a combination of Google Maps and Stata/IC 15.1 software. A statistical analysis comparing the demographics of each town region was also completed using Stata. Results: The maps generated suggest that there may be a disparity in core food accessibility between town regions. The analysis of demographics demonstrated that one town region had a greater proportion of disadvantaged residents, with statistically significant variation between regions. Conclusion: Data visualization and analysis may be a useful tool for clinicians to communicate accessibility information experienced by local residents. This need not be limited to food accessibility and extended to health services.